1997
DOI: 10.1161/01.res.81.5.753
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Meandering Reentrant Wave Fronts to Anatomic Obstacles in the Atrium

Abstract: Acetylcholine chloride (ACh) induces nonstationary meandering reentrant wave fronts in the atrium. We hypothesized that an anatomic obstacle of a suitable size prevents meandering by causing attachment of the reentrant wave front tip to the obstacle. Eight isolated canine right atrial tissues (area, 3.8 x 3.2 cm) were mounted in a tissue bath and superfused with Tyrode's solution containing 10 to 15 mumol/L ACh. Holes with 2- to 10-mm diameters were sequentially created in the center of the tissue with biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 44 publications
7
79
1
1
Order By: Relevance
“…Therefore, the main objective of this work is to present a numerical study of the interaction of spiral waves with obstacles and to show the existence of different transitions due to the presence of obstacles. By considering non-excitable and partially excitable obstacles we will show that obstacles cannot only stabilize the dynamics as shown in (Ikeda et al, 1997;Kim et al, 1999;Lim et al, 2006), but also, they can act as destabilizers. In both cases and by different mechanisms, the obstacle might act as a switch between two arrhythmic regimes, in which one is less dangerous than the other.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, the main objective of this work is to present a numerical study of the interaction of spiral waves with obstacles and to show the existence of different transitions due to the presence of obstacles. By considering non-excitable and partially excitable obstacles we will show that obstacles cannot only stabilize the dynamics as shown in (Ikeda et al, 1997;Kim et al, 1999;Lim et al, 2006), but also, they can act as destabilizers. In both cases and by different mechanisms, the obstacle might act as a switch between two arrhythmic regimes, in which one is less dangerous than the other.…”
Section: Introductionmentioning
confidence: 93%
“…Examples of partially excitable obstacles are scar tissue (Starobin et al, 1996) or ionic heterogeneities (Starobin et al, 1996;Tusscher & Panfilov, 2002;Valderrábano et al, 2000), whereas examples of non excitable obstacles are arteries (Valderrábano et al, 2000) or the natural orifices in the atria (Azene et al, 2001). It has been observed that an obstacle in cardiac tissue might act as a stabilizer of spiral wave dynamics (Davidenko et al, 1992;Ikeda et al, 1997;Kim et al, 1999;Lim et al, 2006;Pertsov et al, 1993;Valderrábano et al, 2000), as it provides a transition between meandering spiral waves (Ikeda et al, 1997) or multiple spiral waves (Shajahan et al, 2007;Valderrábano et al, 2000) into a simple rotation spiral, which is attached to the obstacle. This 17 www.intechopen.com transition is clinically important because as it has been shown, fibrillation like activity changes to a tachycardia regime (Kim et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Par la suite, la réentrée sera pérennisée si le temps nécessaire à la circulation du front est supé-rieur à la période réfractaire partout le long du circuit. On a montré qu'un obstacle, de diamètre aussi petit que 0,6 mm, pouvait ancrer la réentrée 4 dans des cultures de tissu -bien que la dimension minimale fût dix fois plus grande dans l'oreillette du chien [11,12]. Toute modification du tissu qui augmente la probabilité de la formation d'un bloc local ou qui diminue la vitesse de propagation autour d'un obstacle sera favorable au déclenchement et au maintien de réentrées.…”
Section: Microstructure Et Arythmies Auriculaires Arythmies Et Procesunclassified